Analisa Sistem Informasi untuk Proses Permintaan Data pada Universitas XYZ - Angellia Debora Suryawan; Veronica Veronica (ULTIMA InfoSys, 2015)
Data is very important component in the organization and should be managed properly. Information with accurate, precise, and reliable data be beneficial for the organization for decision making. XYZ University realize that the data management is very important process. The needs of data must be supported properly and quickly, so that the required data can be accessed anytime and anywhere. In this study discusses the process of providing data according to user demand. The method in this paper is identification, define the problem, and data collection. XYZ University already has applications to support data requests, but not all data requests can be fulfilled in the system. There is still a process of data requests made through emails. Overall, the application for data requests very helpful for database and system admin staff, so the routine data requests through emails can be reduced. The application has also features for monitoring data requests from units, so the Manager can monitor the process of the data request and find out any unit that doing frequent data requests each month. But, the application also required for tracking data requests, so user can monitor status of data requests, who’s working on, and estimation time for processing data requests. Index Terms - data, data request, database, information system.